An Analysis of the Overlooked Value of Greatness - Beesley, Brandon (Dianoia: The Undergraduate Philosophy Journal of Boston College, 2023)
Greatness is a prevalent topic within philosophy of which many interpretations are offered, ranging from Aristotle's virtue-driven megalopsychos to Nietzsche’s power-hungry übermensch. Humanity’s persisting interest in the idea of greatness is undeniable– the desire for achievement can become obsessive, overwhelming and, for many, anxiety inducing. While there have been innumerable attempts to explain what greatness is, there is little to no scholarship on why we burden ourselves with the pursuit of greatness, consequently and uncharacteristically placing ourselves in a position of angst and vulnerability. The risk of failure and embarrassment loom menacingly behind displays of ambition, seemingly incompatible with the visceral desire for achievement many of us find so familiar. This paper attempts to primarily fill this absence and explore greatness’ value (why we feel the need to strive) while simultaneously remedying errors in prevalent philosophical concepts of greatness. Ideally, an understanding of greatness and its value will offer solace and encouragement for those facing the anxiety and detriment that is all too often concomitant with the human desire for achievement. A coherent conception of greatness and its value will perhaps create an entry point to easing the variety of stresses and pressures that come with the pursuit of greatness. To accomplish this, the paper introduces multiple perspectives from prominent philosophers both of old (Plato, Aristotle, Saint Thomas Aquinas) and more contemporary (Nietzsche, Amy Allen, Virginia Held) through a critical lens. Using relatable, real-world examples that promote interaction from a wide readership, a logical analysis and structural critique of each philosophy is conducted. Finally, a concept is offered that finds both power and virtue are critical, even intrinsic, characteristics of greatness and its value.